2009
DOI: 10.1590/s1516-89132009000500009
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of antibacterial potential of some plants used in indian traditional medicine for the treatment of microbial infections

Abstract: A comparative in vitro antibacterial potential of extracts (aqueous and ethanol) of five important medicinal plants (Aegle marmelos, Azadirachta indica, Terminalia chebula, Mangifera indica and Ocimum sanctum) were investigated using microbial growth inhibition assays against the common human pathogenic bacteria (Staphylococcus aureus, Pseudomonas aeruginosa and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Similar results were obtained in case of M1 bacterium where this microbe was found to be susceptible to S3 extract Chebula extracts S1-S4 were ineffective in inhibiting M3 bacterial growth giving no IZD values. This study is comparable to previously reported results in literature where all the four microbes are effectively inhibited with acetone extract of the plants with variations in IZD values [16].…”
Section: Determination Of Antioxidant Activity Of T Chebula Extractssupporting
confidence: 92%
“…Similar results were obtained in case of M1 bacterium where this microbe was found to be susceptible to S3 extract Chebula extracts S1-S4 were ineffective in inhibiting M3 bacterial growth giving no IZD values. This study is comparable to previously reported results in literature where all the four microbes are effectively inhibited with acetone extract of the plants with variations in IZD values [16].…”
Section: Determination Of Antioxidant Activity Of T Chebula Extractssupporting
confidence: 92%
“…This information is important because, according to Romero et al [26], water is usually the main solvent used by traditional healers to prepare plant extracts, an election solvent that can affect the antibacterial activity of the analyzed extracts. The microbial growth inhibition capacity relies on the rich variety of phytochemicals including flavonoids, tannins, coumarins, terpenoids, triterpenes, alkaloids and vegetable oils (such as eucalyptol), and all compounds can be easily isolated by ethanol, which is a suitable solvent for the extraction of bioactive plant materials [27,28]. In fact, it is important to emphasize that traditional healers can easily use alcohol or aguardiente to prepare the macerations employed in phytotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Midlogarithmic phase organisms were harvested by inoculating this culture into 50 ml of fresh broth for additional 2.5 to 3.5 hrs at 37 0 C. The bacteria were then centrifuged, washed and resuspended in 10 mM cold sodium phosphate buffer (pH=7. 4) 12 . The optical density of an aliquot was measured at 620 nm and the concentration of bacteria were standardized (OD 620 0.20= 5 X 10 7 CFU/ml).…”
Section: Leaves Collection and Processingmentioning
confidence: 99%
“…Chemically, these plant-derived biochemicals have unique built-in chirality due to which they act as natural inhibitor or modulator of biologically vital enzymes and receptors, and this is the reason of their being antimicrobial or immunomodulators [2][3][4][5] . Efforts have been going on throughout the world to discover the new individual or combination of old/new antibacterial agents from various kinds of sources such as micro-organisms, animals, and plants.…”
mentioning
confidence: 99%